Pendampingan Bahasa Inggris bagi Kelompok Tani Stroberi di Desa Pancasari dalam Meningkatkan Daya Saing Pariwisata - Kadek Ayu Ekasani; Ni Made Ayu Natih Widhiarini; Ida Ayu Gayatri Kesumayathi; Ni Putu Dian Nirmala Trisna; Jesyca Amanda Salsabilla; Kadek Thea Kirana; Ni Wayan Putri Kariyani (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2025)
This community service program aims to enhance the English communication skills of strawberry farmers in Pancasari Village, Sukasada District, Buleleng Regency, as an effort to strengthen tourism competitiveness through agrotourism. The activity was carried out through practical English training using a participatory and context-based approach that reflects the farmers’ real communication needs. The training consisted of two main stages: a classroom session employing the role-play method and a field practice session held directly at the strawberry farm with the involvement of local tourists and student assistants. The training materials covered daily expressions commonly used in interactions with visitors, including greetings, product explanation, offering activities, and basic transaction language. The primary learning media were a bilingual communication booklet and situational training modules, both developed from the results of a prior needs analysis. The evaluation results showed a significant improvement in the participants’ English communication abilities. Based on the pre-test and post-test results, the average improvement reached 43%, particularly in speaking confidence, vocabulary mastery, and fluency. Participants also demonstrated increased enthusiasm and professionalism when interacting with tourists in English. This program proves that practical and role-play–based training is effective in developing both linguistic competence and communicative confidence among local farmers. It also strengthens their role as tourism actors who contribute to the sustainable development of the Pancasari agrotourism area.